Immersive Video towards Vocabulary Mastery: EFL Students’ Perspective - Tarisa Olivia Putri; Peptia Asrining Tyas; Widya Caterine Perdhani (Institut Agama Islam Negeri Palopo, 2022)
EFL students have to master vocabulary in order to understand the material in the classroom. However, based on the observation in one of the private junior high schools in Malang, students have low vocabulary and face difficulties in understanding sentences. It happens because the teacher is too focused on using one kind of traditional technique where the book acts as the main source of learning. This case causes the limitation of vocabulary. Therefore, this study aims to find out the students’ perspective on the use of a teaching media for vocabulary mastery namely immersive video. To solve this problem, the researchers formulated a research question, how are students’ opinions towards the use of immersive video in vocabulary mastery? The method used was a mixed method by applying quantitative and qualitative approaches. The participants were 7th graders that consisted of 60 students in total. The data was collected through questionnaires and interviews. The findings show that students enjoy the learning process when immersive video is used. It helps them to remember vocabulary in the long term. In addition, it makes students become more active in learning vocabulary.